Tekstualisasi Dan Kontekstualisasi Hadis Larangan Berpergian Bagi Perempuan Tanpa Mahram - Riky Supratama; Hilalludin Hilalludin (Fikr: Jurnal Pemikiran Studi Islam, 2025)
This research examines the prohibition on women traveling without a mahram from both textual and contextual perspectives. The study begins by presenting the text of a hadith from Sahih Muslim, which states that a woman is not allowed to travel for three days unless accompanied by a mahram. It then explores the concept of mahram in Islam, including kinship, breastfeeding, and marital relations. In the textual analysis phase, the research reviews the opinions of the four major schools of thought (Hanafi, Maliki, Shafi’i, and Hanbali), which generally require the presence of a mahram for women traveling, especially for pilgrimage (hajj). The study also presents variations among scholars regarding the distance allowed for a woman’s journey and the conditions for safe travel. In the contextualization phase, the research critiques the purely textual approach by considering modern contexts where security measures for women have greatly improved. It finds that the original reason for the prohibition was to protect women’s safety and honor, which was relevant to the historical context. Therefore, modern social and security contexts should be considered in implementing the hadith to make its interpretation more relevant to contemporary women’s needs